Analisis Strategi Kepala Sekolah Madrasah Tsanawiyah Swasta di Bekasi dalam Menarik Minat Calon Siswa Baru - Irnie Victorynie; Khumaidi, Ahmad; Umat Lili Hamdani (CV. Creative Tugu Pena, 2024)
This research aims to analyze the strategies of private school principals in Bekasi in attracting prospective new students amidst intense competition between schools using SWOT analysis. The research method uses a qualitative descriptive approach. Data collection through interviews, observation and documentation. The research results show that based on the SWOT analysis, school principals use two strategies in recruiting prospective new students. Namely an internal strategy by improving infrastructure and quality of learning as well as implementing programs that are attractive to students. Meanwhile, external strategies are carried out by collaborating with students, parents and the surrounding community to jointly promote the school.